An Analysis Of Students’ Anxiety In Learning English At The Eleventh Grade Of SMA Negeri 10 Kerinci - Mike Nurmalia Sari; Pretty Elisa Ayu Ningsih (IICLS (Indonesian Institute for Corporate Learning and Studies), 2023)
This study investigates eleven SMAN 10 Kerinci students' English nervousness and what causes it. Both quantitative and qualitative data are in this study. Surveys provide quantitative data, whereas interviews provide qualitative data. SMAN 10 Kerinci eleventh-graders are the study's population. They number 42. Face validity was evaluated on a Hafizi questionnaire utilized in this study. Before calculating the proportion of respondents' achievements each group had, the Miles and Huberman interactive model analysis method was used to qualitatively analyze the data. Two forms of anxiousness were detected in SMAN 10 Kerinci eleventh-graders. About 21.86% of pupils had trait anxiety, while 60.12% had state anxiety. Students are worried about 46.84% the teacher, 29.30% the subject, and 47.87% their own actions. According to this study, teachers should choose the correct technique and materials to reduce student anxiety while learning English. They also recommend that students prepare adequately before English class to avoid anxiety and distraction.